THREE-DIMENSIONAL MODELING OF STRESSED STATE OF MOVING INGOT AT CHANGES OF BOUNDARY TEMPERATURE CONDITIONS - A. Chichko; A. Borozdin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The three-dimensional mathematical model for numerical modeling of stressed and deformed state of ingots that move with a constant speed in a furnace with step heating and given number of temperature zones is proposed in the paper. The paper presents results of computer calculations pertaining to temperature stresses of an ingot that moves with a constant speed in furnaces with six temperature zones.